Evaluating The Effect of Time and Temperature on The Ph, Titratable Acidity &Brix of Pasteurized LowTo-No Nectar Orange Drinks Packed in Paper Based Aseptic Packages - Mohammad, Azeen Kamal Al-Deen; Abdul, Nashmil Ali (Kurdistan Journal of Applied Research, 2022)
Orang drink is the most common flavoured drink consumed in Iraq and it can be found in markets of all sizes and in all provinces making them subjected to a wide range of storage temperature and storage time. In this work, the effect of storage time and temperature was studied on three different local brands of Orange drink with Low-to-No nectar content; all were packed in Laminated Aseptic Cartons (LAC). Samples were stored in a fixed and controlled temperature environment ranging between 10 ?C-50 ?C for a period of 5 weeks and the samples were tested for the values of Brix, Titratable Acidity (TA), and pH at the beginning and at the end of each week. The results showed that no significant difference (p > 0.05) was found, which showed that there is low-to-no evidence that the selected range of storage temperature and time in this study significantly affected the values of Brix, TA, and pH.